Demonstratives and speaker stance in Thai - Khammee, Kultida; Liang-Itsara, Aphiwit; Rhee, Seongha (Journal of pragmatics, 2024)
Demonstratives constitute a language universal. They are primarily spatial but can designate mental space, signaling the speaker's stances in discourse. In stance-taking, e.g., evaluating, positioning, and aligning, (inter)subjectivity plays an essential role. This paper addresses two sets of demonstrative-based discourse markers (DDMs) in Thai, i.e., those based on the proximal demonstrative nîi (▪) and the medial demonstrative nân (▪), focusing on their functions and positionality at left periphery (LP) and right periphery (RP). An examination of the functional distribution of eight DDMs in our Thai dataset reveals that the oft-cited LP/RP Functional Asymmetry Hypothesis is not supported. Further worth noting is that the Leftward Movement often said to be associated with subjectification (i.e., increasing subjectification pushes a word to move leftward) is not attested, or at least not observable, in the development of DDMs in Thai. •Thai has demonstrative-based discourse markers (DDMs).•DDMs developed from proximal and medial demonstratives.•DDMs carry diverse subjective and intersubjective functions.•The Functional Asymmetry Hypothesis is not supported by the DDM development.•The Leftward Movement Hypothesis is not supported in the DDM development.